Perfil hematológico de los trabajadores de la minería del oro expuestos a vapores de mercurio metálico en el municipio de Amalfi, Antioquia (2010)
ABSTRACT: he complete blood count (hemoleucogram) is a test that provides information on the health status of an individual, and may be altered in gold mining workers who are chronically exposed to metallic mercury vapors. Objective To determine the hematologic profile in gold mining workers from Amalfi, Antioquia, chronically exposed to metallic mercury vapours. Materials and methods This study included 41 miners and seven workers from the gold trading industry exposed to metallic mercury vapors (paired with 48 unexposed subjects in accordance with individual characteristics). A complete blood count was done for each participant, as well as a peripheral blood smear and mercury detection in urine after 24 hours. Results Gold mining workers had a mean concentration of 59.7 μg/L of mercury in their urine, and were found to have multiple qualitative (morphological) and quantitative abnormalities in their complete blood count. Of these abnormalities, the values of hemoglobin, mean corpuscular hemoglobin (MCH) and mean corpuscular hemoglobin concentration (MCHC), showed a statistically significant difference between the groups of exposed and unexposed individuals (p<0.05). Conclusions There is a possible relationship between exposure to metallic mercury vapors and alterations in the differential white blood cell count, hemoglobin and red blood cell indices; however, additional studies are needed to confirm the effect of this metal on hematopoietic homeostasis.